SOCIOSCIENTIFIC ISSUE (SSI) LEARNING IN 8TH GRADE SCIENCE LESSONS - Zikra Zikra; Arief Muttaqiin (Pendidikan IPA, FMIPA, UNP, 2023)
This study aims to determine the implementation of Socioscientific Issue (SSI) learning in class VIII science lessons at SMP Pembangunan Laboratorium UNP in the 2022/2023 Academic Year. This study uses a description method by observing the learning that researchers do. Observations were made by three observers who observed the learning process by filling out observation sheets regarding the learning process from the opening, this activity, to the closing of the lesson. The sample of this research was 32 students of class VIII A at SMP Pembangunan Laboratorium UNP. The research data that has been obtained is analyzed in the form of percentages and then described descriptively. Based on the results obtained, it can be concluded that the implementation of Socioscientific Issue (SSI) learning has been carried out well, seen from the implementation carried out by the teacher with a percentage of implementation of 92%, but in practice there are students who are not focused and feel bored in learning so that the expected abilities are not achieved.